A Qualitative Research On English Speaking Programs At Islamic Boarding School - Amiruddin; Fitriah; Macksalmina Mulya (JURNAL ILMIAH MAHASISWA, 2023)
The purpose of this study is to identify students’ perception toward English speaking program, namely conversation and to find out the purpose of the programs implementation. Qualitative research method was used. Fifty students of two classes from the third grade were purposively taken for the sample of this study. To answer the research question” what are the students’ perception toward Islamic Boarding School speaking programs in improving their speaking skills ?” questionnaires were distributed to know the students’ perception the implemented speaking program. After collecting the data, the results of this study shows that the students had many kinds of perception toward the implemented speaking program. Fifty students had different points of view on the speaking activities that they participated. In this regard, most of students agreed that conversation activities improved their speaking skills and gave them a lot of benefit s in their learning even though a few number of them disagreed. Generally, the purpose of speaking programs are: (a) to familiarize students to speak English, (b) to train students to speak fluently and confidently, (c) to give chance to students to practice speaking and (4) to create a good environment learning speaking in the target language.